Influence of pH on the release of nickel ions from fixed orthodontic appliances in artificial saliva - Youssouf Ouédraogo; Abdoul Karim Sakira; Moussa Ouédraogo; Issa Tapsoba; Tarcissus Konsem; Jean Bertin Beugré (Journal of Orthodontic Science)
AIM: The aim of this study was to make a laboratory assessment of pH influence on the kinetics of the release of nickel ions in artificial saliva. METHODS AND MATERIAL: In this study, 15 basic orthodontic appliances are immersed in 15 polyethylene tubes each containing 40 ml of artificial saliva. Tubes were divided into three sub-groups of 5 tubes depending on the pH: pH 5, pH 7 and pH 8. The release of nickel ions was measured using atomic absorption spectrometry in a sample of 5 ml of artificial saliva taken one hour, four hours and one hundred and sixty-eight hours after immersion in a water bath at 37°. STATISTICAL ANALYSIS USED: Significance threshold P was set at 0.05. A Student T test and the 2-way Anova test (with a Bonferoni post-test) were used respectively to compare the means. RESULTS: The neutral pH causes a low release of nickel ions. The release kinetics of nickel ions is minimal for neutral pH, it increases when pH varies. After one hour of immersion, the nickel released did not reach the spectrometer quantification threshold as for neutral and acid pH. The alkaline pH causes an average release of nickel ions from the beginning without kinetic variation. As time passes (T3), the acidic pH causes more nickel ions release through a succession of oxidation-reduction reactions. After 168 hours, the average mass of nickel released is 0.30 µg for pH 7, 1.35 µg for pH 8 and up to 2.85 µg for pH 5. CONCLUSIONS: Quantities released did not reach nickel toxicity threshold in humans. Orthodontists must consider the potential risk of hypersensitivity due to nickel in fixed orthodontic appliances.